Right ventricular longitudinal strain for risk stratification in low-flow, low-gradient aortic stenosis with low ejection fraction. Issue 7 (13th January 2016) - Dahou, Abdellaziz; Clavel, Marie-Annick; Capoulade, Romain; Bartko, Philipp Emanuel; Magne, Julien; Mundigler, Gerald; Bergler-Klein, Jutta; Burwash, Ian; Mascherbauer, Julia; Ribeiro, Henrique B; O'Connor, Kim; Baumgartner, Helmut; et al.
Abstract : Background: Left ventricular global longitudinal strain (LVLS) is a powerful predictor of outcome in patients with low-flow, low-gradient aortic stenosis (LF-LG AS) and low LV ejection fraction (LVEF). However, the impact of right ventricular (RV) function on the outcome of these patients remains unknown. Objectives: The aim of this study was to examine the impact of RV function as evaluated by RV free wall longitudinal strain (RVLS) on mortality in patients with LF-LG AS and low LVEF. Methods: 211 patients with LF-LG AS (mean gradient <40 mm Hg and indexed aortic valve area (AVA) ≤0.6 cm 2 /m 2 ) and low LVEF (≤40%)) were prospectively recruited in the True or Pseudo-severe Aortic Stenosis study. AS severity was assessed using the projected AVA (AVAproj ) at normal flow rate. Among the 211 patients, 128 had RVLS measurement available at rest and were included in this analysis. RVLS measurement at dobutamine stress echocardiography (DSE) was available in 58 of the 128 patients. Results: Two-year survival was lower in patients with RVLS<|13|% (53%±9%) compared with those with RVLS>|13|% (69%±5%) (p=0.04). In multivariable Cox analysis stratified for the type of treatment (aortic valve replacement vs conservative) and adjusted for age, AS severity, previous myocardial infarction and LVLS, rest RVLS<|13|% (HR=2.70; 95% CI 1.19 to 6.11; p=0.018) was independently associated with all-cause mortality. RVLS had incremental prognostic value over baseline risk factors and LVLS (χ 2 =20.13 vs 13.56; p=0.01). Reduced stress RVLS was also associated with increased risk of mortality (stress RVLS<|14|%: HR=2.98; 95% CI 1.30 to 6.52; p=0.01). In multivariable Cox analysis, stress RVLS<|14|% remained independently associated with mortality (HR=2.94; 95% CI 1.23 to 7.02; p=0.015). After further adjustment for rest RVLS, stress RVLS<|14|% remained independently associated with mortality (HR=3.29; 95% CI 1.17 to 9.25; p=0.024), whereas rest RVLS was not (p>0.05). Conclusions: In this series of patients with LF-LG AS and low LVEF, reduced RVLS was independently associated with increased risk of mortality. Furthermore, stress RVLS provided incremental prognostic value beyond that obtained from rest RVLS. Thus, RVLS measurement at rest and at DSE may be helpful to enhance risk stratification in this high-risk population. Trial registration number: NCT01835028; Results.